Speculations of Immunotherapy in COVID-19 Patients with Practical Applications During Childhood and Pregnancy - Al-Momen, Hayder; Jasim, Shaymaa Kadhim; Al-Ameri, Laith Thamer (AL-Kindy College Medical Journal, 2020)
The rapid spread of novel coronavirus disease (COVID19) throughout the world without available specific treatment or vaccine necessitates alternative options to contain the disease. Historically, children and pregnant women were considered high-risk population of infectious diseases but rarely have been spotlighted nowadays in the regular COVID-19 updates, may be due to low global rates of incidence, morbidity, and mortality. However, complications did occur in these subjects affected by COVID-19. We aimed to explore the latest updates of immunotherapeutic perspectives of COVID-19 patients in general population and some added details regarding pediatric and obstetrical practice. Immune system boosting strategy is one of the recently emerging issues allowing the body defense mechanism to produce virus-neutralizing antibodies to counteract the viral impacts on multiple organ damage. Measles vaccination (which is universally used for children in many countries, but contraindicated during pregnancy) could urge the body to produce these antibodies which may apply their effects through cross-reactivity of measles vaccine and COVID-19 antigenic proteins. In addition, intravenous immunoglobulin and convalescent plasma could have such neutralizing antibody effect leading to clinical improvement and viral elimination. Pediatric and obstetrical experience has appeared in previous publications. Human monoclonal antibodies are the future promising approach to treat and prevent COVID-19 with the use of tocilizumab in recent studies. Pediatric data are still in progress while no pregnancy ongoing trials are planned up to date. The better understanding of the host antiviral response may pave the way to develop immunotherapeutic plans against COVID-19 in the near upcoming days.